TEKNIK SUPERVISI PENDIDIKAN - Meti Fatimah; Yoga Wicaksono; Aulia Arsinta (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
Supervision is a systematic assessment method for the entire phase of the teaching process. Educational supervision plays an important role in improving the quality of teaching and learning. It is positioned as a planned activity aimed at improving the educational situation and the overall quality of education. This paper aims to find out the basic principles and objectives in the practice of educational supervision, to find out the techniques of educational supervision, and to find out the benefits and challenges in educational supervision. This paper uses an individual supervision approach and a group supervision approach. Educational supervision has evolved from a traditional inspection approach to a more scientific, collaborative process, and centered on teacher professional development and improving the quality of teaching and learning. Various techniques, both individual and group, offer different ways to support teachers in their professional journey. The benefits of educational supervision are extensive, including improving the quality of teaching, teacher professional development, increasing understanding of educational goals, and fostering leadership.